2002
DOI: 10.1128/cdli.9.6.1160-1164.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to Bile-Tolerant Helicobacter Species in Patients with Chronic Liver Diseases, a Randomized Population Group, and Healthy Blood Donors

Abstract: Bile-tolerant Helicobacter species such as Helicobacter pullorum, Helicobacter bilis, and Helicobacter hepaticus are associated with hepatic disorders in animals and may be involved in the pathogenesis of chronic liver diseases (CLD) in humans. Antibody responses to cell surface proteins of H. pullorum, H. bilis, and H. hepaticus in serum samples from patients with CLD, a randomized population group, and healthy blood donors were evaluated by using enzyme linked immunosorbent assay (ELISA). The results were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Cross-reactivity between bile-tolerant species and H. pylori has been documented previously (1). Several aspects of the study design limit the interpretation of the results: the two laboratories used different strains of H. pylori, with none originating from the Thai population investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-reactivity between bile-tolerant species and H. pylori has been documented previously (1). Several aspects of the study design limit the interpretation of the results: the two laboratories used different strains of H. pylori, with none originating from the Thai population investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a subset of EHS also cause persistent infections associated with chronic inflammation and neoplasia, which is analogous to the association between H. pylori infection and subsequent chronic gastritis and gastric cancer (3). There is growing evidence that EHS can be associated with chronic liver diseases in humans, including chronic hepatitis, liver carcinoma, chronic cholecystitis, and cholangiocarcinoma (1,2,12,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is growing evidence that different murine helicobacters may be associated with human infection and disease, including H. bilis and H. hepaticus (1,8,17,18,20), other murine helicobacter species have yet to be incriminated as potential zoonotic agents. Mouse helicobacter infections are particularly insidious, as they seldom produce clinical signs or lesions in immunocompetent mice.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, 4 of 14 biliary tract cancer patients tested positive for H. bilis DNA by PCR (18). In addition to PCR, serologic studies have shown that human patients with chronic liver diseases, including autoimmune liver disease, developed antibodies to H. bilis and H. hepaticus (1,20).…”
mentioning
confidence: 99%